#1**0 **

Solve for x:

2 (4 + 2 (3 - 5 x)) = 5 (2 + 2 (3 - 3 x))

2 (3 - 5 x) = 6 - 10 x:

2 (6 - 10 x + 4) = 5 (2 + 2 (3 - 3 x))

Add like terms. 4 + 6 = 10:

2 (10 - 10 x) = 5 (2 + 2 (3 - 3 x))

2 (3 - 3 x) = 6 - 6 x:

2 (10 - 10 x) = 5 (6 - 6 x + 2)

Add like terms. 2 + 6 = 8:

2 (10 - 10 x) = 5 (8 - 6 x)

Expand out terms of the left hand side:

20 - 20 x = 5 (8 - 6 x)

Expand out terms of the right hand side:

20 - 20 x = 40 - 30 x

Add 30 x to both sides:

30 x - 20 x + 20 = (30 x - 30 x) + 40

30 x - 30 x = 0:

30 x - 20 x + 20 = 40

30 x - 20 x = 10 x:

10 x + 20 = 40

Subtract 20 from both sides:

10 x + (20 - 20) = 40 - 20

20 - 20 = 0:

10 x = 40 - 20

40 - 20 = 20:

10 x = 20

Divide both sides of 10 x = 20 by 10:

(10 x)/10 = 20/10

10/10 = 1:

x = 20/10

The gcd of 20 and 10 is 10, so 20/10 = (10×2)/(10×1) = 10/10×2 = 2:

**Answer: |x = 2**

Guest Mar 27, 2017